A concept mapping study evaluating the UK's first NHS generic fatigue clinic. (1st September 2015) - Hackett, Katie L.; Lambson, Rebecca L.; Strassheim, Victoria; Gotts, Zoe; Deary, Vincent; Newton, Julia L
Abstract: Importance: Fatigue is a significant and debilitating symptom affecting 25% of the population. It occurs in those with a range of chronic diseases, can be idiopathic and in 0.2–0.4% of the UK population occurs in combination with other symptoms that together constitute chronic fatigue syndrome (CFS). Until recently, NHS clinical services only focussed upon CFS and excluded the majority of fatigued patients who did not meet the CFS diagnostic criteria. The CRESTA Fatigue interdisciplinary clinic was established in 2013 in response to this unmet need. Objective: To identify the service needs of the heterogeneous group of patients accessing the CRESTA Fatigue Clinic, to prioritize these needs, to determine whether each is being met and to plan targeted service enhancements. Design: Using a group concept mapping approach, we objectively identified the shared understanding of service users accessing this novel clinic. Setting: NHS Clinics for Research & Service in Themed Assessment (CRESTA) Fatigue Clinic, Newcastle Upon Tyne, UK. Participants: Patients ( n  = 30) and referrers ( n  = 10) to the CRESTA Fatigue Clinic contributed towards a statement generation exercise to identify ways the clinic could support service users to improve their quality of life. Patients ( n  = 46) participated in the sorting and rating task where resulting statements were sorted into groups similar in meaning and rated for 'importance' and 'current success'. Main outcome and measure: We mapped the needs of patients attending the CRESTA Fatigue Clinic and identified which high‐priority needs were being successfully met and which were not. Results: Multidimensional scaling and hierarchical cluster analysis depicted the following eight themed clusters from the data which related to various service‐user requirements: 'clinic ethos', 'communication', 'support to self‐manage', 'peer support', 'allied health services', 'telemedicine', 'written information' and 'service operation'. Service improvement targets were identified within value bivariate plots of the statements. Conclusion and Relevance: Service development concepts were grouped into thematic clusters and prioritized for both importance and current success. The resulting concept maps depict where the CRESTA Fatigue Clinic successfully addresses issues which matter to patients and highlights areas for service enhancement. Unmet needs of patients have been identified in a rigorous service evaluation, and these are currently being addressed in collaboration with a service‐user group.